DISC INTEGRATION METHOD TO DETERMINE THE VOLUME OF A ROTARY OBJECT TWO DIMENSIONAL - Adin Nadiya Ifati (Perwira Journal of Science & Engineering, 2022)
Integral is a concept of continuous addition in mathematics. In the problem of calculus, integral include the main operations used in calculations. One of the integral aplications in real problems is to calculate the volume of a rotating object. The object is 2 dimensional object than is rotated be 3 dimensional based its rotary axes. The first step is to draw a graph or curve of an equation given in the Cartesian plane and its boundaries. Then determine the concept of rotation about the y-axis or x-axis. Furthermore, one must be able to understand well the steps in calculating the volume of rotating object with an integral